2002
DOI: 10.1046/j.1365-2788.2002.00401.x
|View full text |Cite
|
Sign up to set email alerts
|

Mental health services and young people with intellectual disability: is it time to do better?

Abstract: The development of mental health services for this vulnerable group with complex psychiatric and behaviour disorders has been poor for a number of reasons, including lack of recognition at the primary care level and insufficient numbers of trained professionals within specialist services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
48
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(49 citation statements)
references
References 9 publications
0
48
1
Order By: Relevance
“…In such cases, behavioral crisis can reflect a disparity between the needs of the person with ID, and the service system's provision of supports. These healthcare inequities have been identified in many countries (Dekker & Koot, 2003;Frahn, et al 2006;Krauss, Gulley, Sciegaj, & Wells, 2003;McCarthy & Boyd, 2002;Ouellette-Kuntz, 2005). In Australia for instance, it is estimated that although 40% of children with ID are identified with comorbid psychopathology, only 10% receive mental health care (Einfeld et al, 2006), an inequity that certainly predisposes an individual to behavioral crisis.…”
mentioning
confidence: 99%
“…In such cases, behavioral crisis can reflect a disparity between the needs of the person with ID, and the service system's provision of supports. These healthcare inequities have been identified in many countries (Dekker & Koot, 2003;Frahn, et al 2006;Krauss, Gulley, Sciegaj, & Wells, 2003;McCarthy & Boyd, 2002;Ouellette-Kuntz, 2005). In Australia for instance, it is estimated that although 40% of children with ID are identified with comorbid psychopathology, only 10% receive mental health care (Einfeld et al, 2006), an inequity that certainly predisposes an individual to behavioral crisis.…”
mentioning
confidence: 99%
“…Authors from many industrialized nations, including Canada, have identified mental health care in this population as an addressable health inequity (Dekker & Koot, 2003;Irish College of Psychiatrists, 2004;Krauss, Gulley, Sciegaj, & Wells, 2003;McCarthy & Boyd, 2002;Ouellette-Kuntz, 2005;Oullette-Kuntz et al, 2005).…”
mentioning
confidence: 99%
“…Comorbid disorders among children with ID have been least understood and have not garnered the attention of most research on individuals with disabilities to date (Campbell and Malone 1991;McCarthy and Boyd 2002). General psychiatric and health care services lack adequate experience and knowledge in the assessment and treatment of individuals with ID (Sturmey et al 2007).…”
Section: Interventions and Clinical Implicationsmentioning
confidence: 99%